A Rare Case of Porocarcinoma and Trichoblastoma Arising in a Nevus Sebaceus of Jadassohn - Drew C. Mitchell; Gina J. Kuehn; Glynis A. Scott; Timothy D. Doerr; Francisco Tausk (Case Reports in Dermatological Medicine)
Nevus sebaceus of Jadassohn, or “organoid nevus,” is a common, benign hamartoma of the skin consisting of epithelial and adnexal components. Its natural history and association with neoplastic growths is well documented. The majority of concomitant neoplasms are benign—trichoblastoma and syringocystadenoma papilliferum are most frequently discovered—but malignant tumors have been described. We present the case of a 58-year-old male with a congenital nevus sebaceus of Jadassohn on his left parietal scalp that had been enlarging, changing color, and bleeding over the prior year. Clinical exam and histology disclosed the presence of a trichoblastoma and porocarcinoma arising within the nevus sebaceus. Porocarcinoma is a rare, intermediately aggressive, malignant eccrine gland tumor that is frequently metastasized at presentation. Otolaryngology performed wide local resection with sentinel lymph node biopsy. This case highlights the diversity of tumors associated with nevus sebaceus of Jadassohn, potential for malignant expansion, and necessity for close monitoring and maintaining a low threshold for biopsy in evolving lesions.